1966
DOI: 10.1104/pp.41.10.1610
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Changes in Respiratory Pathways in Cortland Apple Skin During Storage

Abstract: Sumnmnary. Ontogenic changes in respiratory pathways of skinls of detached apple fruits were measuired duiring a 4 month period. ReEtults showsed that an increase in pentose pathway occuirred with increasing senescence in this tisstue. V-ariation in temperature at any given age did not result in an alteratioin of the C,1C, ratio. atory determinatioins %-ere removedl from storage and tisedl 1 houir after warming to room temperatulre. Twice cl(iring storage a larger sample was removed aind heldl for I week at 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Total respiration of young tissue is high, whereas the old tissue respires at a low rate (8). The pentose phosphate activity of young tissues is low, but it increases with age (3,5,9,12,16,18). The permeability of young tissue is well controlled, but, with age, the free space of the tissue and its leakiness increase (4,13).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Total respiration of young tissue is high, whereas the old tissue respires at a low rate (8). The pentose phosphate activity of young tissues is low, but it increases with age (3,5,9,12,16,18). The permeability of young tissue is well controlled, but, with age, the free space of the tissue and its leakiness increase (4,13).…”
Section: Resultsmentioning
confidence: 99%
“…In developing a procedure for extracting RNA from pear buds, we found that unknown substances in the brown scales interfered with the extraction of nucleic acids from the central (3,5,9,12,16,18). Buds also contain a substantial amount of fatty material (6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations